Sox-9 transient transfection enhances chondrogenic expression of osteoarthritic human articular chondrocytes in vitro: preliminary analysis - Sha'ban, Munirah; Osman Cassim, Samsudin; Mohd Yahya, Nor Hamdan; Saim, Aminuddin; Idrus, Ruszymah (Korean Tissue Engineering and Regenerative Medicine Society, 2011)
In this study, we are taking step to actively manage osteoarthritis that may help gain control over osteoarthritic pain and delay the degenerative changes in articular cartilage in future. We transiently over expressed cartilage transcriptional factor, human sox-9 gene in chondrocytes derived from consented osteoarthritic patients after joint surgery. The expression vector carrying human sox-9 gene, pAdTrack-sox9 was transformed into One Shot TOP 10 Chemically Competent E. coli according to the manufacturer protocol. Plasmid purification was performed in accordance with QIAGEN (R) plasmid purification kit procedure. We compared the efficiency between two transfection techniques i.e. lipofection using Lipofectamine (TM) 2000 kit from Invitrogen, USA and nucleofection using Human Chondrocytes Nucleofector (R) kit from Amaxa Biosystem, Germany. Chondrocytes were cultured and transfected with sox-9 gene at passage 1 according to the manufacturers' protocols. Transfected chondrocytes were expanded until passage 3. Expression of chondrogenic markers namely collagen type H, aggrecan core protein and sox-9 were evaluated by quantitative RT-PCR method using iScript (TM) One Step RT-PCR Kit with SYBR Green, BIO-RAD. Chondrogenic dedifferentiation marker, collagen type I was also analyzed using the quantitative RT-PCR method. Expression level of each targeted gene was normalized to the housekeeping gene, human glyceraldehyde-3-phosphate dehydrogenase (GAPDH). Overall efficiency ranging from 50% to 60% could be achieved using both transfection techniques. Transiently transfecting cells demonstrated remarkable competency sustaining specific chondrogenic genes namely collagen type H, aggrecan core protein and sox-9, significantly better than in the non-transfected cells. It is believed that this preliminary finding has to be extended to develop its full potential since sox-9 transcription factor is essential for chondrocyte differentiation and cartilage formation. Sox9 gene therapy would delay the degenerative changes in articular cartilage which is consistent to the up-regulation of cartilage-specific markers especially collagen type II synthesis in vivo.